PENAMBAHAN LIMBAH IKAN PATIN (Pangasius sp.) PADA PAKAN TERHADAP KADAR ALBUMIN DAN PERTUMBUHAN IKAN GABUS (Channa striata) - Ainun Mardhiyyah; Faddilla Amalia; Muhammad Azhari; Inggried Sinaga; Syarah Putri Pratami; Retno Cahya Mukti (Universitas Sriwijaya, 2023)
Snakehead fish (Channa striata) is one of fish type that has the potential to be cultivated. The albumin levels in snakehead fish are the main attraction for consumers. Albumin which usually comes from human blood has a fairly expensive price. Therefore, an alternative is needed to produce albumin at a lower cost. One of the efforts that can be done is to increase the growth as well as the albumin content in snakehead fish through feeding rich in protein content. One source of high protein that is still not widely used by the community comes from fish waste where it is known that fish waste contains high protein and has the potential to be a source of fish feed raw materials. This study aims to determine the best dose of catfish offal flour in feed to increase albumin levels as well as growth in snakehead fish and help reduce pollution levels from fish waste. The experimental design carried out was a completely randomized design (CRD) consisting of 4 treatments and 3 replications consisting of P1: 0%, P2:10%, P3:20%, and P4:30%. The results showed that P1 was the best result with albumin levels of 12.73 mg/mL, absolute length growth of 1.17 cm, absolute weight growth of 1.2 g, and survival of 79.17%. The maintenance water quality measured during the study was the temperature ranged from 26.5-27.4°C, pH ranged from 6.7-7.1, and dissolved oxygen ranged from 5.25-5.56 mg/L. Keywords: albumin, fish waste, snakehead fish